2016
DOI: 10.1007/s10111-016-0396-9
|View full text |Cite
|
Sign up to set email alerts
|

From cockpit to operating theatre to drilling rig floor: five principles for improving safety using simulator-based exercises to enhance team cognition

Abstract: For over 30 years, aviation has conducted training courses to enhance team performance and improve safety involving simulation with observation and directed feedback. Participants' performance is observed by trained and experienced observers who then provide feedback using behaviour-based evidence noted during the simulator exercise. More recently, in healthcare, operating theatre personnel have adopted simulator-based training (SBT), observation and feedback for learning and practice to reduce the potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…In particular, taking on a situated action approach, the research questions concern how the participants are orienting towards general instructions from the prospective briefing phase in the subsequent scenario and debriefing phases of training, considering how the social and material resources in the simulator environment organize the learning activities. As highlighted by Button et al (2015), Suchman showed that instructions are always accountable in action, occasioned by and contingent on realizing them.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, taking on a situated action approach, the research questions concern how the participants are orienting towards general instructions from the prospective briefing phase in the subsequent scenario and debriefing phases of training, considering how the social and material resources in the simulator environment organize the learning activities. As highlighted by Button et al (2015), Suchman showed that instructions are always accountable in action, occasioned by and contingent on realizing them.…”
Section: Introductionmentioning
confidence: 99%
“…Communication in surgical teams affects safety in surgery, and a misunderstanding may put the patient's life at stake. It is comparable to the specific demands of the communication between the members of the crew in the cockpit of an aircraft, where the safety of the passengers may be at stake, or in a nuclear plant, where a communication error may lead to a life‐threatening situation for the population (Chrichton, ). It is easy to understand that such workplaces require competent professionals capable of communicating in a safe mode using words explicitly understood by everyone in the team for safety and to avoid fatal errors.…”
Section: Discussionmentioning
confidence: 97%
“…To enhance safe care and to reduce adverse events, it is essential that both technical and non‐technical skills are performed in the OT (Mitchell et al, ). Safe care in the OT is dependent on mutual understanding of specific concepts in communication among everyone in the team (Chrichton, ). Communication in surgical teams affects safety in surgery, and a misunderstanding may put the patient's life at stake.…”
Section: Discussionmentioning
confidence: 99%
“…Cambridge University Press ( 2021 ) termed simulation as “a model of a set of problems or events that can be used to teach someone how to do something, or the process of making such a model”. Simulators, as we know them in present day industrial context, have been in use for many years in safety critical industries such as aviation, process, health care, nuclear, maritime, and rail to prepare the personnel in these domains for their job roles and to ensure that they perform optimally as a team in instances of highly stressful situations (Crichton 2017 ). Technological advancement has steadily increased the effectiveness of simulators and brought a wide array of advantages to prospective seafarers, as elaborated and summarized in the following Table 1 .…”
Section: The Use Of Simulators In Maritime Education and Trainingmentioning
confidence: 99%